Peran Pendidikan Profesi Advokat Dalam Memahami Dan Mengaplikasikan Hukum Hak Kekayaan Intelektual - Ai Kusmiati Asyiah; Arif; Mila Karmila (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
The dynamic development of regulations in Indonesia, particularly in the field of Intellectual Property Rights (IPR), demands preparedness from future law enforcers, including prospective advocates. Prospective advocates in Tasikmalaya, as part of the next generation of legal professionals, require a comprehensive and up-to-date understanding of IPR to contribute to creating legal certainty and fostering innovation in the digital era. The aim of this community service program is to enhance the general understanding and practical capacity of prospective advocates in Tasikmalaya regarding IPR through an intensive online training program. The partners in this activity were a number of prospective advocates undergoing the Special Education for Advocate Profession (Pendidikan Khusus Profesi Advokat - PKPA). The methods used included literature study for material preparation, initial needs assessment, interactive online training via Zoom, group discussions, collaborative case analysis using Google Docs, and evaluation through pre-tests, post-tests, and legal document drafting projects. The training results showed a significant improvement in participants' understanding, with the average post-test score (82.4) far exceeding the pre-test (58.5), reflecting a 40.9% increase in comprehension. Participants also demonstrated improved practical skills in drafting legal opinions and electronic lawsuit drafts. The satisfaction survey recorded a score of 4.6 out of 5. This program successfully equipped prospective advocates with a strong and relevant IPR foundation, which is expected to improve the quality of legal services and IPR enforcement in Indonesia in the future. This activity underscores the importance of continuous IPR education from an early stage in the legal profession curriculum.